Proceedings of the 3rd International Conference on Frontiers of Intelligent Computing theory and applications (FICTA) 2014 - Satapathy, Suresh Chandra; Biswal, Bhabendra Narayan; Udgata, Siba K.; Mandal, J. K. (Springer International Publishing, 2015)
This volume contains 95 papers presented at FICTA 2014: Third International Conference on Frontiers in Intelligent Computing: Theory and Applications. The conference was held during 14-15, November, 2014 at Bhubaneswar, Odisha, India.  This volume contains papers mainly focused on Data Warehousing and Mining, Machine Learning, Mobile and Ubiquitous Computing, AI, E-commerce & Distributed Computing and Soft Computing, Evolutionary Computing, Bio-inspired Computing and its Applications.